Glycine plays a crucial role as a co-agonist of NMDA receptors in the neuronal circuit generating body movements in rat fetuses - Shimomura, Hideki; Ito, Mari; Nishiyama, Ayae; Tanizawa, Takakuni; Takeshima, Yasuhiro; Nishimaru, Hiroshi; Arata, Akiko (Neuroscience research, 2015)
•We examined the contribution of glycine to the perinatal rat spinal circuit.•We used isolated brainstem-spinal cord-upper limb preparation from perinatal rat.•We focused on the developmental changes of forelimb movements as a fetal movement.•Glycine generated fetal movement via the glycine binding site of NMDA receptor.•Fetal movement was suppressed by strychnine-sensitive glycine receptor after birth. Neuronal circuits generating fetal movements in mammals are localized in the brainstem and the spinal cord. It has been shown that glycine plays an important role through the strychnine-sensitive glycine receptors in these circuits. However, the role of glycine as the NMDA receptor co-agonist in fetal period is not fully understood. In this study, we examined the contribution of glycine to the perinatal rat spinal circuit generating forelimb movements utilizing isolated brainstem-cervical-spinal-cord preparations. In late embryonic-days-preparations, spontaneous motor bursts related to forelimb movements (forelimb-movement-related bursts; FMRBs) and respiration-related activity were observed. In neonatal preparations, spontaneous FMRBs were not observed but periodic motor bursts resembling the FMRBs could be induced after bath application of strychnine (strychnine-induced motor bursts; SIMBs). Both FMRBs and SIMBs were blocked by either the NMDA receptor antagonist APV or the antagonists of the glycine binding site of NMDA receptors [5,7-dichlorokynurenic acid (DCKA) or L-689560]. Furthermore, these motor bursts were facilitated by the glycine uptake blocker sarcosine. This effect of sarcosine was blocked by DCKA. The findings indicate that glycine plays a crucial role as a NMDA receptor co-agonist in generating spontaneous fetal motor activity before functioning as a classical inhibitory neurotransmitter in suppressing the fetal neuronal circuits.